مقترح علاجي للإنتاج الكتابي عند تلاميذ السنة الخامسة ابتدائي (ابتدائية نصيرة الهاشمي 1 نموذجا - طير، سليمة, حواس، أسماء (Univerity of Eloued, 2022)
لاشك أن الأداء اللغوي الكتابي السليم يحفظ للغة رونقها وحسنها، لذلك هدفت دراستنا إلى الكشف عن واقع الأداء الكتابي لمتعلمي السنة الخامسة ابتدائي، ومعرفة المعيقات والصعوبات وأسبابها والسبل التي تعين نمو هذا الأداء لدى التلاميذ، فكان اختيارنا لهذه الفئة من التلاميذ عن قصد كونها تتوج المرحلة الابتدائية، ونظرا لتفشي ظاهرة الضعف في نشاط الإنتاج الكتابي ارتأينا أن نبحث عن السبل لعلاج هذه الظاهرة وبعد خوضنا العديد من التجارب والدراسات والورشات الميدانية، ومن خلال الأهمية البالغة لنشاط الإنتاج الكتابي فجاء بحثنا الموسوم بـ: "مقترح علاجي للإنتاج الكتابي عند تلاميذ السنة الخامسة ابتدائي" وصفوة القول أنه يجب الإسراع في عملية أعادة النظر في المناهج والإيمان العميق بمشروع ترقية اللغة العربية والاستمرارية في تطوير أساليب تعليمها وطرق توصيلها للناشئة بما يواكب العصر. There is no doubt that proper written linguistic performance preserves the language of its splendor and beauty, so our study aimed to reveal the reality of the written performance of the fifth year primary learners, and to know the obstacles and difficulties and their causes and the ways that help the growth of this performance among the students, so we chose this group of students on purpose. Being the culmination of the primary stage, and due to the prevalence of the phenomenon of weakness in the activity of written production, we decided to look for ways to treat this phenomenon and after conducting many experiments, studies and field workshops, and through the great importance of the written production activity, our research came marked with: “A therapeutic proposal for written production when Students of the fifth year of primary school” and the best is to say that the process of reconsidering the curricula must be accelerated, the deep belief in the project of promoting the Arabic language and the continuity of developing its teaching methods and ways of delivering it to young people in line with the times
Keywords: مقترح علاجي، الانتاج الكتابي، تلميذ سنة خامسة; Proposition thérapeutique, production écrite, étudiant de cinquièmeannée